Safety of single-dose primaquine as a Plasmodium falciparum gametocytocide: a systematic review and meta-analysis of individual patient data - Stepniewska, K; Allen, EN; Humphreys, GS; Poirot, E; Craig, E; Kennon, K; Yilma, D; Bousema, T; Guerin, PJ; White, NJ; Price, RN; Raman, J; et al. (BioMed Central, 2022)
Background In 2012, the World Health Organization (WHO) recommended single low-dose (SLD, 0.25 mg/kg) primaquine to be added as a Plasmodium (P.) falciparum gametocytocide to artemisinin-based combination therapy (ACT) without glucose-6-phosphate dehydrogenase (G6PD) testing, to accelerate malaria elimination efforts and avoid the spread of artemisinin resistance. Uptake of this recommendation has been relatively slow primarily due to safety concerns. Methods A systematic review and individual patient data (IPD) meta-analysis of single-dose (SD) primaquine studies for P. falciparum malaria were performed. Absolute and fractional changes in haemoglobin concentration within a week and adverse effects within 28 days of treatment initiation were characterised and compared between primaquine and no primaquine arms using random intercept models. Results Data comprised 20 studies that enrolled 6406 participants, of whom 5129 (80.1%) had received a single target dose of primaquine ranging between 0.0625 and 0.75 mg/kg. There was no effect of primaquine in G6PD-normal participants on haemoglobin concentrations. However, among 194 G6PD-deficient African participants, a 0.25 mg/kg primaquine target dose resulted in an additional 0.53 g/dL (95% CI 0.17–0.89) reduction in haemoglobin concentration by day 7, with a 0.27 (95% CI 0.19–0.34) g/dL haemoglobin drop estimated for every 0.1 mg/kg increase in primaquine dose. Baseline haemoglobin, young age, and hyperparasitaemia were the main determinants of becoming anaemic (Hb < 10 g/dL), with the nadir observed on ACT day 2 or 3, regardless of G6PD status and exposure to primaquine. Time to recovery from anaemia took longer in young children and those with baseline anaemia or hyperparasitaemia. Serious adverse haematological events after primaquine were few (9/3, 113, 0.3%) and transitory. One blood transfusion was reported in the primaquine arms, and there were no primaquine-related deaths. In controlled studies, the proportions with either haematological or any serious adverse event were similar between primaquine and no primaquine arms. Conclusions Our results support the WHO recommendation to use 0.25 mg/kg of primaquine as a P. falciparum gametocytocide, including in G6PD-deficient individuals. Although primaquine is associated with a transient reduction in haemoglobin levels in G6PD-deficient individuals, haemoglobin levels at clinical presentation are the major determinants of anaemia in these patients. Trial registration PROSPERO, CRD42019128185